Analysis of pathological features of lymph node in adult-onset Still disease - Ting CHEN; Yingyong HOU; Xiaowen GE (Zhongguo Linchuang Yixue)
ObjectiveTo summarize the pathological morphological features, diagnosis, and differential diagnosis of adult-onset Still disease (AOSD), and to improve clinical understanding of the disease. MethodsA retrospective analysis was conducted on the morphological characteristics, immunophenotypes, and molecular detection results of lymph node biopsies from three AOSD patients. ResultsCase 1: lymph node biopsy tissue showed significant lymphoid follicular hyperplasia, accompanied by parafollicular hyperplasia; the germinal centers exhibited a starry-sky phenomenon, with no obvious histiocyte proliferation foci, plasma cells, or neutrophils; immunohistochemical staining showed that CD3 and CD5 T lymphocyte were positive in the paracortical area, CD20 and CD79α markers showed that B lymphocytes were mainly located in the follicular area, CD21 follicular dendritic cells and CD68 histiocytes were positive. Case 2: lymph node puncture tissue showed paracortical hyperplasia, a decrease in the number of follicles, and a reduction of follicular volume; there were no obvious histiocyte proliferation foci, plasma cells, or neutrophils; immunohistochemical staining showed positive CD3, CD5 T lymphocytes in the paracortical area, and CD20, CD79α B lymphocytes in the follicular region. Case 3: lymph node puncture tissue showed partial preservation of the normal lymph node structure, the paracortical area was diffusely proliferated, and the histiocyte hyperplasia was patchy with partial necrosis, and obvious nuclear debris, scattered plasma cells and eosinophils can be seen and no obvious neutrophil infiltration in the necrotic area; immunohistochemical staining of case 3 showed that CD21 and CD23 follicular dendritic cells were positive, and Bcl-2, Bcl-6, CD3, CD5, CD20, CD79α, and multiple myeloma protein 1 (MUM1) were positively expressed in some lymphocytes; the Ki-67 proliferation index was high, approximately 70%; a few plasma cells were positive for CD138, with individual cells positive for CD1α; CD10 and CyclinD1 were negative; histiocytes were positive for myeloperoxidase (MPO); and EBER was negative for in situ hybridization. The results of TCR gene rearrangement and IG gene rearrangement in the three cases were negative.ConclusionThe immunophenotype of AOSD is diversity, and its dignosis depends on the clinical and pathological morphological features and immunophenotype, excluding infectious diseases, malignant tumors and lymphoma, etc.